Frequência escolar e políticas de escolarização em Minas Gerais nas primeiras décadas republicanas (1892-1911) - Fabiana de Oliveira Bernardo (2020)
This thesis aims to understand the construction of the importance of school attendance in the organization of primary public school (Minas Gerais, Brazil) in the context of the first republican decades. We seek to verify how the policies to encourage school attendance were being built during the surveyed period and how do they related to the construction of the republican school. We seek to identify the actions undertaken by the Legislative and Executive powers regarding to the maintenance of students in schools. It is plausible to reflect on school attendance as a matter of political scope, because we understand the public school as a vector that is part of the construction of the state itself in the first decades of the republican regime in Minas Gerais. In the course of the investigation, we noticed that the meanings attributed to school attendance were being constructed in the investigated period. The starting point is in the year of 1892, in which the first republican law of instruction of Minas Gerais was promulgated, the Law No. 41. The endpoint is 1911, when there was the education reform governed by Decree No. 3191. We consider that the fact that the educational legislation of 1911 makes the school fund compulsory is an arrival point where school attendance has came to be seen by the State as an issue that should undergo a kind of intervention that goes beyond the pedagogical, structural and administrative offer of the school. We seek to understand the process that culminated in a specific regulation for increasing school attendance. We used two main documental corpora in this research: the first comes from the public administration from which we selected reports from the Interior Secretarial and messages from State Presidents. The second is legislation that can be considered as an instrument of society organization. We analyzed the Federal Constitution of 1891, the Minas Gerais Constitution of 1892, the primary education reforms edited between 1892 and 1911, namely, Law No. 41 regulated by Decree No. 655 of October 17, 1893; Law No. 281 of 1899, regulated by Decree No. 1.348 in January of 1900; Law No. 439 of 1906, regulated by Decree No. 1.960 in 1906 and Law No. 533 of 1910 regulated by Decree No. 3.191 of June 9, 1911, as well as the Proceedings of the Legislative Assembly and News from the Minas Gerais Newspaper that dealt with the frequency and the school fund. The educational reforms undertaken in Minas Gerais, the decrees that organize the laws, as well as the debates held by legislators in this context, give us clues about the school social function and about the importance of strategies creation to increase school attendance. With this thesis, therefore, we try to demonstrate the process in which attendance was becoming a central element in schooling policies in Minas Gerais in the late Nineteenth and early Twentieth century’s, more specifically, in the advent of the Republic in Brazil.